Oxide multilayer thermoelectric generators. Issue 3 (6th November 2017) - Töpfer, Jörg; Reimann, Timmy; Schulz, Thomas; Bochmann, Arne; Capraro, Beate; Barth, Stefan; Vogel, Andy; Teichert, Steffen
Abstract: Oxide multilayer thermoelectric generators (MLTEG) were fabricated, using the standard multilayer technology. Green tapes of p‐type La2 CuO4 and n‐type Nd2 CuO4 thermoelectric oxides were stacked with intermediate insulating glass layers. Electrical contacts between thermoelectric oxides were applied, using screen‐printing of AgPd paste, and multilayers were cofired at 1000°C. However, cofiring of four different materials turned out to be very challenging, and contact resistance problems frequently led to device malfunctions. We developed a new concept of a transversal multilayer thermoelectric generator (TMLTEG), which is characterized by a simple design. This generator is build up by stacking layers of a p‐ or n‐type thermoelectric oxide and printing stripes of AgPd paste onto the thermoelectric layers at an angle with respect to the temperature gradient. Transversal multilayer thermoelectric generators were fabricated using p‐type La2 CuO4, or n‐type substituted CaMnO3 ; cofiring of the multilayer stacks was performed at 1000°C. The TMLTEG based upon p‐type lanthanum cuprate exhibits a power output of 7.8 mW at ∆ T = 200 K in the low temperature range of 25‐135°C. Materials issues, cofiring characteristics, design and the thermoelectric performance of multilayer TEGs will be discussed.